Tikanga rikue: as íntimas ligações na tradução de Vidas Secas para língua indígena - Ribeiro, João Paulo (Universidade Federal de São Carlos, 2018)
The objective of this work is to present a stage of experience in the translation of Vidas secas (RAMOS, [1938] 2015) to the Nheengatu, indigenous language spoken by the Baré, Baniwa and Werekena ethnicities in the Upper Rio Negro. On the interest of translation appeared visions. We name it by prophetic of translation to this experience with worlds. For this translator, the geography of thought will represent a technique of shifts on the meeting places of the worlds in the power of intimate-connections active. It is for a new place that we believe has passed by adopting relations between shamanism and translation.
Tikanga rikue: the Intimate-connections in the translation of Vidas Secas for indigenous language
Keywords: Tradução em línguas indígenas; Profética da tradução; Xamanismo; Tradução; Translation in indigenous languages; Prophetic of translation; Shamanism; Translation; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::FISIOLOGIA DA LINGUAGEM